2015
DOI: 10.1177/0960327115573596
|View full text |Cite
|
Sign up to set email alerts
|

Effects of airborneAspergilluson serum aflatoxin B1 and liver enzymes in workers handling wheat flour

Abstract: Objective: The present work aimed to investigate the relationship between occupational exposure to airborne molds, serum aflatoxin B1 (AFB1), and liver enzymes of workers handling wheat flour. Methods: The study included 90 bakers, 100 flour milling workers, and 100 controls with no exposure to flour dust. Workplace aspects such as temperature and relative humidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 17 publications
3
21
1
Order By: Relevance
“…But in contrast to the present study, Saad-Hussein et al [20] revealed that there was no significant difference in ALP levels between the workers and the controls. This could be attributed to the inclusion of all the milling workers with high and low levels of serum AFB1/alb in the study, while, in the present study only milling workers with high serum levels of AFB1/alb were included.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…But in contrast to the present study, Saad-Hussein et al [20] revealed that there was no significant difference in ALP levels between the workers and the controls. This could be attributed to the inclusion of all the milling workers with high and low levels of serum AFB1/alb in the study, while, in the present study only milling workers with high serum levels of AFB1/alb were included.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, in the previous study, the liver enzymes AST and ALT of workers handling wheat flour were found to be significantly elevated compared to the controls, and these elevations were significantly increased with the increase in the environmental exposures to Aspergillus flavus [20]. But in contrast to the present study, Saad-Hussein et al [20] revealed that there was no significant difference in ALP levels between the workers and the controls.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Another shortcoming of ELISA is that it relies on specific antibodies for each mycotoxin; therefore, it is not appropriate for multi-mycotoxin determination. In fact, ELISA was applied in just 15% of all studies reviewed [73][74][75][76][77][78][79].…”
Section: Mycotoxin Determination In Human Blood Plasma and Serummentioning
confidence: 99%
“…Occupational exposure to aflatoxin was found in textile workers and was associated with liver tumor biomarkers (Saad-Hussein et al, 2013). Airborne Aspergillus was associated with higher serum aflatoxin B1 and several liver enzymes among workers handling wheat flour (Saad-Hussein et al, 2016) as well, suggesting workers for several occupations may be at increased risk for indoor mold exposures.…”
Section: At Risk Populationsmentioning
confidence: 99%